Dutch Guideline on Knee Arthroscopy Part 2: non-meniscus intraarticular knee injury: a multidisciplinary review by the Dutch Orthopaedic Association - Koëter, Sanfer; Van Tienen, Tony G; Rijk, Paul C; Vincken, Patrick W J; Segers, Michiel J M; van Essen, Bert; van Melick, Nicky; Stegeman, Bernadine H; van Arkel, Ewoud R A (Acta Orthopaedica, 2020)
Background and purpose — A guideline committee of medical specialists and a physiotherapist was formed on the initiative of the Dutch Orthopedic Association (NOV) to update the Guideline Arthroscopy of the Knee: Indications and Treatment 2010. This next Guideline was developed between June 2017 and December 2019. In part 1 we focused on the meniscus; this part 2 addresses all other aspects of knee arthroscopy. Methods — The guideline was developed in accordance with the criteria of the AGREE instrument (AGREE II: Appraisal of Guidelines for Research and Evaluation II) with support of a professional methodologist from the Dutch Knowledge Institute of Medical Specialists. The scientific literature was searched and systematically analyzed. Conclusions and recommendations were formulated according to the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) method. Recommendations were developed considering the balance of benefits and harms, the type and quality of evidence, the values and preferences of the people involved, and the costs. In this part 2 we focus on anterior knee pain, patellar tendinopathy, the role of arthroscopy in the osteoarthritic knee, arthroscopy and patellar dislocation, and osteochondral fractures, and additionally ask what the role is of arthroscopy in bacterial arthritis or ligamentous injury of the knee, and whether arthroscopy is supplemental in the treatment of tibial plateau fractures. We did not address the role of arthroscopy in the discoid meniscus and osteochondritis dissecans in children. The guideline is published online, in Dutch, and is available from the Dutch Guideline Database (https://richtlijnendatabase. nl/?query=Artroscopie+van+de+knie+&specialism=)